Antidiabetic and Analgesic Effects of Glycosmis pentaphylla (Retz.) in Swiss Albino Mice - Khatun, Most. Chand Sultana; Mia, M Ripon; Ali, M Ashraf; Rahman, M Moshiur; Begum, Khadiza; Begum, Kohinur (Ibrahim Medical College Journal, 2013)
Background and purposes: Glycosmis pentaphylla (Retz.) Correa, a medicinal plant is popularly used as herbal remedy for various ailments in Bangladesh. It was also reported that GP has both anti-hyperglycemic and analgesic effects and being widely used to reduce blood glucose and to alleviate pain for many years in this region though published literatures are scarce. The present study was designed to evaluate whether ethanolic extract of Glycosmis pentaphylla (GP) have antihyperglycemic and analgesic effects. A total of 60 Swiss Albino male mice of nine weeks (weight, 20-25g) were used for investigation. Of them, 40 were made diabetic by alloxan. They were investigated in two groups a) 20 mice by oral glucose tolerance test (4 samples OGTT) at 0, 30, 90 and 120 min; and b) 20 mice for a week-long antihyperglycemic activity on day 0, 1, 3 & 7. Both the groups were subdivided into four, each having 5 mice i) the control received only 0.5% methyl cellulose as vehicle; ii) Standard received vehicle plus metformin; iii & iv) test DGP250 & DGP500 received vehicle plus GP extract with 250 & 500 mg /kg, respectively. For the analgesic activity, 20 mice were investigated in four subgroups, each having 5 mice and similar steps were adopted. Here, vehicle was used 1% Tween 80 and intra-peritoneal injection of Acetic acid for eliciting pain in all four subgroups. The standard group got diclofenac sodium for comparison with the test groups GP250 and GP500. In OGTT, Ethanolic extract of GP250 and GP500 reduced blood glucose at 90 min. But the levels of reduction were more significant at 120 min, 50.7% by GP250 and 66% by GP500 (p<0.001). The reduction is almost comparable with that induced by metformin. Likewise, for a weeklong anti-hyperglycemic activity, the GP extracts were found as equally effective as metfomin, which was also dose dependent. In addition to antihyperglycemic effect, the ethanolic extract of GP showed significant analgesic effect that was also dose dependent. Our results indicate that GP extract has antihyperglycemic effect in both short and in weeklong duration, which is almost comparable to Metformin HCL, a known and widely used antihyperglycemic agent. The GP extract was also found to have an analgesic effect almost comparable to diclofenac sodium, a known analgesic drug. Further study is needed to confirm the anti-hyperglycemic and analgesic effect of GP including its side effects in long term use. DOI: http://dx.doi.org/10.3329/imcj.v6i1.14721 Ibrahim Med. Coll. J. 2012; 6(1): 21-26